Animation Canva-Based PP-SDA Platform: Synergy of Islamic Education and Science in IPAS Learning in MI/SD - Akhmad Dalil Rohman; Tri Unggul Sari Asih; Uki Adi Prasetiya (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
Learning Natural and Social Sciences (IPAS) in elementary schools requires instructional media that can contextually explain the interrelationships between scientific concepts, social phenomena, and the values of Islamic Primary Education. However, classroom practices are still predominantly dominated by conventional and static media, which inadequately support student engagement and understanding. This study aims to develop the PP-SDA Platform based on Canva Animation as an interactive and visual IPAS learning medium integrated with Islamic values in the topic of Natural Resource Management. The research employed a Research and Development (R&D) approach using the 4D model, which includes the stages of defining, designing, and developing. The defining stage involved curriculum analysis, review of learning outcomes, initial observations, and communication with teachers to identify media needs and learner characteristics. The designing stage produced content concepts, presentation flow, and storyboard-based visual designs, which were developed into a PowerPoint-based prototype using Canva Animation. The development stage included prototype production and limited trials conducted with fourth-grade students of MI Salafiyah Sidorejo using student and teacher response questionnaires as research instruments. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically. The results indicate that the PP-SDA Platform demonstrates high levels of attractiveness, clarity of content, integration of Islamic values, and usefulness, with average scores of 89.60% from students and 91.60% from teachers. The media also enhances students' attention, understanding, and ability to relate scientific concepts to Islamic moral values. Therefore, the PP-SDA Platform is feasible to be used as an innovative learning medium in IPAS instruction.